Improving the Measurement of Iron(III) Bioavailability in Freshwater Samples: Methods and Performance. (20th December 2022) - Balsamo Crespo, Emiliano; Reichelt‐Brushett, Amanda; Smith, Ross E. W.; Rose, Andrew L.; Batley, Graeme E.
Abstract: The toxicity of iron(III) in fresh waters has been detected at concentrations above the iron solubility limit, indicating a contribution of colloidal and particulate forms of iron(III) to the toxicity response. Current water quality guideline values for iron in fresh water are based on analytical determinations of filterable or total iron. Filtration, however, can underestimate bioavailable iron by retaining some of the colloidal fraction, and total determinations overestimate bioavailable iron measurements by recovering fractions of low bioavailability from suspended solids (e.g., iron oxides and oxyhydroxides) naturally abundant in many surface waters. Consequently, there is a need for an analytical method that permits the determination of a bioavailable iron fraction, while avoiding false‐negative and false‐positive results. Ideally, a measurement technique is required that can be readily applied by commercial laboratories and field sampling personnel, and integrated into established regulatory schemes. The present study investigated the performance of pH 2 and pH 4 extractions to estimate a bioavailable iron(III) fraction in synthetic water samples containing iron phases of different reactivities. The effects of aging on fresh precipitates were also studied. The total recoverable, 0.45‐µm filtered, and pH 4 extractable fractions did not discriminate iron phases and age groups satisfactorily. Contrastingly, the pH 2 extraction showed specificity toward iron phases and aging (0.5–2‐h interval). Extraction times above 4 h and up to 16 h equally recovered >90% of the spiked iron regardless of its age. Furthermore, <1% of the well‐mineralized iron was targeted. The present study shows that a pH 2 dilute‐acid extraction is a suitable candidate method to operationally define iron fractions of higher bioavailability avoiding false‐negative and false‐positive results. Environ Toxicol Chem 2023;42:303–316. © 2022 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.